Meaning Construction Of K-Pop Dance Cover Members - Lathifah, Nisa; Permana, Putih Pusti; Hanafi; Reza, Faisal (Yayasan Sinergi Kawula Muda, 2023)
K-pop dance cover is an activity where individuals or groups replicate the dance movements of Korean idol groups, as done by the K-pop dance cover community called HD Girls. This research aims to understand the experiences, motives, and meanings related to the self-concept of HD Girls members. Members of the HD Girls community, when performing a dance cover, must be able to adjust their appearance to match the K-pop idols they are covering. Therefore, as community members, they can interpret themselves as individuals who can align their appearance with the characteristics of the K-pop idols they are covering. The research employs a qualitative method with Alfred Schutz's phenomenological approach. Data collection techniques include primary data (interviews and observations) and secondary data (books, journals, and documentation). Informants were selected using purposive sampling, and data validity was ensured through source triangulation. The findings reveal that HD Girls members have various experiences in K-pop dance cover, such as making friends, paying more attention to their appearance, promoting K-pop idol groups, gaining self-confidence, feeling comfortable in social interactions, and feeling satisfied when receiving compliments. From these experiences, certain motives were identified: the